2018
DOI: 10.1002/ece3.3786
|View full text |Cite
|
Sign up to set email alerts
|

Within trophic level shifts in collagen–carbonate stable carbon isotope spacing are propagated by diet and digestive physiology in large mammal herbivores

Abstract: Stable carbon isotope analyses of vertebrate hard tissues such as bones, teeth, and tusks provide information about animal diets in ecological, archeological, and paleontological contexts. There is debate about how carbon isotope compositions of collagen and apatite carbonate differ in terms of their relationship to diet, and to each other. We evaluated relationships between δ13Ccollagen and δ13Ccarbonate among free‐ranging southern African mammals to test predictions about the influences of dietary and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 69 publications
6
40
0
2
Order By: Relevance
“…The lower than expected values in ε* bioapatite-keratin observed in some Amazonian primary consumers might be explained in a similar way. Other studies have also shown highly variable ε* bioapatite-protein values within a free-ranging herbivore mammalian community ( 39 ), as well as ε* bioapatite-protein poorly distinguishing trophic levels ( 40 ), suggesting that the ε* bioapatite-protein within dietary categories (especially among primary consumers) should not be expected to be uniform.…”
Section: Discussionmentioning
confidence: 99%
“…The lower than expected values in ε* bioapatite-keratin observed in some Amazonian primary consumers might be explained in a similar way. Other studies have also shown highly variable ε* bioapatite-protein values within a free-ranging herbivore mammalian community ( 39 ), as well as ε* bioapatite-protein poorly distinguishing trophic levels ( 40 ), suggesting that the ε* bioapatite-protein within dietary categories (especially among primary consumers) should not be expected to be uniform.…”
Section: Discussionmentioning
confidence: 99%
“…One possible approach to determine the CH 4 strategy of a larger number of species could be the diet-bioapatite carbon isotope enrichment offset. Studies in which such data have been applied to herbivores have implied a difference in CH 4 emissions between herbivore digestion types (Codron et al, 2018;Tejada-Lara et al, 2018). However, the data from Codron et al (2018) suggest little differences between the hindgut fermenters rock hyrax, black and white rhinoceros (Diceros bicornis, Ceratotherium simum), warthog (Phacochoerus africanus) or even a zebra species (Equus quagga) and ruminants.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies in which such data have been applied to herbivores have implied a difference in CH 4 emissions between herbivore digestion types (Codron et al, 2018;Tejada-Lara et al, 2018). However, the data from Codron et al (2018) suggest little differences between the hindgut fermenters rock hyrax, black and white rhinoceros (Diceros bicornis, Ceratotherium simum), warthog (Phacochoerus africanus) or even a zebra species (Equus quagga) and ruminants. The data from Tejada-Lara et al (2018) potentially corroborate the finding of CH 4 emission in arvicoline rodents (voles) of the present study and indicate little difference between the hindgut fermenters African elephant (Loxodonta africana), the black rhinoceros, the horse, a zebra species (Equus burchelli ) and the pig and the ruminants giraffe (Giraffa camelopardalis), Bactrian camel and guanaco (Lama guanicoe).…”
Section: Limitationsmentioning
confidence: 99%
“… Ref, literature sources: 1 – this study; 2 – Codron et al (); 3 – Codron et al (, and sources therein)); 4 – Sponheimer et al (); 5 – Cerling et al (); 6 – Cerling et al (). …”
Section: Methodsmentioning
confidence: 92%
“…These data represent 11 of the 19 species for which faecal data are available, comprising data from specimens collected in the field or sampled from the skeletal collections at the Florisbad Quaternary Research Station of the National Museum, Bloemfontein, South Africa. Most ( n = 75) of these data were from the literature (Codron et al , ; Codron et al , ) with a smaller subset of unpublished data ( n = 58) analysed following the procedures, including isolation of the collagen phase and lipid extraction, described in Codron et al ().…”
Section: Methodsmentioning
confidence: 99%